ANALISIS PERJANJIAN LISAN DALAM JUAL BELI SUSU ANTARA KUD CEPOGO DENGAN PETERNAK SAPI DI KECAMATAN CEPOGO - Syafiq Al’afif Setia Adi; Muhammad Fauzan Hidayat; Burham Pranawa (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2025)
This study discusses the practice of oral agreements in the sale and purchase of milk between the Village Unit Cooperative (KUD) Cepogo and dairy cattle farmers in Cepogo District. The legal relationship between both parties is based on oral agreements that have been passed down through generations, rooted in mutual trust and the familial values inherent in cooperatives. The research aims to analyze the validity, legal force, and juridical implications of such oral agreements, including the risk of default and the dispute resolution mechanisms employed. The method used is an empirical juridical approach, with data collected through interviews, field observations, and document analysis. The findings indicate that the oral agreements fulfill the legal requirements for a valid contract as outlined in Article 1320 of the Indonesian Civil Code (KUHPerdata) and are therefore legally binding. However, the absence of written documentation weakens the position of the parties in the event of disputes, particularly in terms of legal proof. As a result, legal education for both farmers and cooperatives is needed, as well as the preparation of simple supporting documents to enhance legal protection and ensure greater legal certainty in milk trade practices at KUD Cepogo.